Evidencias de validez de la escala para la Evaluación de la Vinculación Afectiva y la Adaptación Prenatal (EVAP) en gestantes usuarias del INMP - Artica-Martínez, José (2019)
The purpose of this instrumental research was to develop evidence of duration and reliability for the evaluation of affective attachment and prenatal adaptation (EVAP) in a pregnant population of the National Maternal Perinatal Institute. Participation of pregnant, adolescent and adult research (N = 310), from the second trimester of pregnancy; That is, starting at 14 weeks. The findings of the study concluded that the six proposed dimensions for the representation of microdimensions of the constructs of adaptation and prenatal affective bonding; Therefore, its subdivision is not required, but a single structure with two dimensions is needed. The final version of the scale was made up of 21 items, twelve integrated the Adaptation to pregnancy dimension and nine formed the dimension Prenatal affective bonding. The confirmatory factor analysis showed that this version of the escalation presents the best adjustment benefits compared to the theoretical proposal and the structure suggested by the exploratory factor analysis without omission of items. Finally, in terms of the reliability of the scale, values of .746 and .749 were obtained for the Adaptation to pregnancy and Affective Linking dimensions, respectively. These values were estimated through the omega coefficient that is suitable for the subscales.